Innovative Approach to Estimating Costs of Vehicle Parking Services - Vnukova, N.M.; Tokhtamysh, T.O.; Yagolnitskiy, O.A.; Hranko, K.B. (Наука та інновації, 2020)
Introduction. The analysis of the state of the vehicle parking system in Ukraine has shown that the organizational, regulatory, and financial conditions of its operation do not meet the needs of road users, user requirements and European practices. Problem Statement. Due to the congestion of the street and road network of large cities of Ukraine by vehicles, there is a need to substantiate and determine zoning indicators to establish the appropriate cost of services for the use of paid parking lots. Purpose. Development of zoning indicators when calculating the cost of services for the use of sites for paid parking of vehicles. Materials and Methods. General and special methods of economic theory, scientific knowledge are used: system, comparative analysis, etc. Results. According to the results of experiments on the load of day platforms for paid parking of vehicles, 3 zones have been identified. Most of the sites fall into Zone I and Zone II because of their load level of more than 60%. The zoning indicators have been developed for the calculation of the cost of services for the use of sites for the payment of parking vehicles. When assessing the priority of the influential factors on the zoning indicator, the scale of relative importance of T. Saati is used. It has been determined that zoning is the main factor influencing the step of adjusting the tariff rate for paid parking of vehicles. The results of the calculations showed that the step of adjusting the tariff should be 0.4. Conclusion. The development can be used in the work of utilities that provide vehicle parking services, in particular, in the preparation and submission of settlement materials and documents for the formation of tariffs for services for the use of daytime parking lots for paid parking.